THE RELATIONS OF ISLAM AND POLITICS (A Study of the Response of Indonesian Muslim Intellectuals Against the Islamic State of Indonesia) - Masruhan Kholil; Sujito _ (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2015)
Problems arising from the relationship between Islam (dîn) and politics (siyâsah) became the polemics among Muslim political thinkers that have not been completely solved up until now. Hence, it is difficult to identify which countriy such as Turkey, Egypt, Sudan, Morocco, Saudi Arabia, Pakistan, Algeria, and Indonesia, that deserves to be a representation of an Islamic state. The consequence of different understandings about the relationship between Islam and politics – in the case in Indonesia- is the emergence of Indonesian Islamic State (NII). This movement attracted a number of responses from Indonesian Muslim intellectuals. Using a sociohistorical-politics approach in discussing these responses as they do not agree about the establishment of the NII, will lead to an understanding of coercion and oppression of understanding group that is different from other groups.